Proceedings of 2023 Chinese Intelligent Systems Conference Volume III - Jia, Yingmin; Zhang, Weicun; Fu, Yongling; Wang, Jiqiang (Lecture Notes in Electrical Engineering, 2023)
XI, 880 p. 430 illus., 340 illus. in color.